2015
DOI: 10.1158/1535-7163.mct-14-0970
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Using c-Myc–Conjugated Nanoparticles Suppresses Breast and Colorectal Cancer Models

Abstract: In this article, we report the development and preclinical validation of combinatorial therapy for treatment of cancers using RNA interference (RNAi). RNAi technology is an attractive approach to silence genes responsible for disease onset and progression. Currently, the critical challenge facing the clinical success of RNAi technology is in the difficulty of delivery of RNAi inducers, due to low transfection efficiency, difficulties of integration into host DNA and unstable expression. Using the macromolecule… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…RNA concentration and integrity were determined by measuring the absorbance at 260 nm. The cDNA was performed using 5 μg of total RNA, 200 U of Superscript III, and 0.5 μg of oligo dT (12)(13)(14)(15)(16)(17)(18) under the following conditions: 42˚C for 90 min, followed by heating at 70˚C for 10 min. The cDNA obtained was amplified using Taq DNA polymerase (Life Technologies) and Wt1 primers: 5'-AACGCCCCTTCATGTGTGC-3' and 5'-GCTGGTCTGAACGAGAAAACCTTC-3' to amplify a fragment of 150 bp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA concentration and integrity were determined by measuring the absorbance at 260 nm. The cDNA was performed using 5 μg of total RNA, 200 U of Superscript III, and 0.5 μg of oligo dT (12)(13)(14)(15)(16)(17)(18) under the following conditions: 42˚C for 90 min, followed by heating at 70˚C for 10 min. The cDNA obtained was amplified using Taq DNA polymerase (Life Technologies) and Wt1 primers: 5'-AACGCCCCTTCATGTGTGC-3' and 5'-GCTGGTCTGAACGAGAAAACCTTC-3' to amplify a fragment of 150 bp.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, WT1 is considered a good target for anticancer therapy (12). The silencing of genes involved in proliferation and apoptosis are an attractive strategy for the development of anticancer therapies (13)(14)(15), and for sensitizing tumor cells to chemotherapy (14). It has been observed that silencing genes such as B-cell lymphoma 2 (BCL2) and BCL-xL sensitizes cisplatin-resistant cells (16,17).…”
mentioning
confidence: 99%
“…However, the used 21 base siRNA duplexes were quite unstable. ShRNAs with a transient period of expression are better suited for long-term effectiveness, due to their ability to produce siRNAs continuously within cancer cells, thus resulting in prolonged suppression of target genes[ 126 ]. Until today, shRNAs have been delivered effectively in vivo using viral vectors.…”
Section: Anti-cancer Therapeutic Aspects Of C-myc In the Colonmentioning
confidence: 99%
“…Furthermore, the effectiveness of this therapy was validated for in vivo tumor suppression using transgenic mouse models. It was found that oral delivery of the c-Myc- conjugated nanoparticles to an Apc -deficient crypt progenitor colon cancer model resulted in an increased host survival and re-entered intestinal tissue to a non- Wnt -deregulated state[ 126 ]. According to these results, it seems that careful design of nonviral nanoparticles may help to made RNA interference technology an affordable and amenable therapy for CRC.…”
Section: Anti-cancer Therapeutic Aspects Of C-myc In the Colonmentioning
confidence: 99%
“… 9 For example, Tangudu et al. 10 reported that upregulation of p53 using anti-miR-21 ASOs linked to rhodamine-labeled nanoparticles and could suppress a CRC model. Kasiri et al.…”
Section: Introductionmentioning
confidence: 99%